Supervisi Klinis Berjenjang Sebagai Upaya Pemberian Asuhan Keperawatan yang Aman Terhadap Pasien - Dahlia, Ade Irma; Novieastari, Enie; Afriani, Tuti (School of Nursing, Faculty of Medicine and Health Science, Universitas Lambung Mangkurat, 2020)
The hospital is required to conduct an evaluation of nursing clinical competence accompanied bystrengthening of direction and monitoring of clinical performance by the nurse manager to ensuring thatnurses are competent so that they can provide safe and appropriate nursing care according to professionalstandards. The purpose of this study is to socialize and evaluate the implementation of multilevel clinicalsupervision guidelines and SOP at RS X. The method is used pilot study through Kurt Lewin's theory ofchange with problem analysis using fishbone diagrams. The unfreezing phase is carried out by collectingdata on the results of the assessment ofmanagement problems through interviews, observations and surveys.The movement phase is doing all the change processes that are written in the form of Plan of Action (POA)with the hospital. The refreezing phase The refreezing stage, namely guidance and SPO for nursingsupervision, was endorsed by the hospital. Implementation is given as a solution to the problem that ismaking guidelines and SPO clinical supervision of tiered nursing. The recommendation for the hospital is toprovide clinical supervision training for the head nurse and primary nurses, socialization of the improvedsupervision instruments and add clinical supervision as a performance indicator for the head nurse andprimary nurses.